Cell cycle exit during bortezomib‐induced osteogenic differentiation of mesenchymal stem cells was mediated by Xbp1s‐upregulated p21Cip1 and p27Kip1. Issue 16 (6th July 2020) - Zhang, Dan; Fan, Rong; Lei, Li; Lei, Lei; Wang, Yanmeng; Lv, Nan; Chen, Ping; Williamson, Ramone A.; Wang, Baiyan; Hu, Jinsong
Abstract: Mesenchymal stem cells (MSCs) are multipotent cells capable of differentiating into a variety of cell types. Bortezomib, the first approved proteasome inhibitor used for the treatment of multiple myeloma (MM), has been shown to induce osteoblast differentiation, making it beneficial for myeloma bone disease. In the present study, we aimed to investigate the effects and underlying mechanisms of bortezomib on the cell cycle during osteogenic differentiation. We confirmed that low doses of bortezomib can induce MSCs towards osteogenic differentiation, but high doses are toxic. In the course of bortezomib‐induced osteogenic differentiation, we observed cell cycle exit characterized by G0 /G1 phase cell cycle arrest with a significant reduction in cell proliferation. Additionally, we found that the cell cycle exit was tightly related to the induction of the cyclin‐dependent kinase inhibitors p21 Cip1 and p27 Kip1 . Notably, we further demonstrated that the up‐regulation of p21 Cip1 and p27 Kip1 is transcriptionally dependent on the bortezomib‐activated ER stress signalling branch Ire1α/Xbp1s. Taken together, these findings reveal an intracellular pathway that integrates proteasome inhibition, osteogenic differentiation and the cell cycle through activation of the ER stress signalling branch Ire1α/Xbp1s.